Internet of Things Based Water Quality Control System - I Putu Andika Putra; Kadek Suar Wibawa; Gusti Made Arya Sasmita (Jurnal Indonesia Sosial Teknologi, 2024)
Fish incubation, which involves the hatching of fish eggs, represents the process of embryogenesis until the embryo emerges from its protective shell. This intricate developmental journey is influenced by a combination of internal and external factors. External factors can be influenced by water quality that is not suitable for hatching fish eggs. Water quality, which includes temperature, dissolved oxygen, light intensity, salinity, and pH, is an important and limiting factor for living creatures that live in water, including chemical, biological, and physical factors. Poor water quality can prevent fish eggs from hatching and even cause death. The primary objective here is the creation of an Internet of Things (IoT)-based system designed for controlling water quality during fish incubation. This system is intended to aid fish farmers in effectively control the environmental conditions within their incubation ponds. The method used in designing IoT device is research and development, and it uses the Arduino Mega microcontroller as the main device to run pH sensors, turbidity sensors, oxygen sensors, temperature sensors, and relay modules. Water Quality Control System The fish incubation was successful. The average time needed to change the water temperature from 28.5 to 29 degrees Celsius is 4 minutes and 7 seconds; change the dissolved oxygen level from 11 to 11.5 is 3 minutes and 33 seconds; change the pH value of the water from 6.9 to 7.1; and maintain turbidity below 5 with an average time of 5 minutes and 58 seconds. Controlling water quality can speed up the fish egg incubation process for 8 hours.